Coding Agricultural Education for Innovative Information and Communication Technology in Colleges of Education in Benue and Nasarawa States, Nigeria - Ekele, Garba Emmanuel (International Journal of Computing Sciences Research, 2020)
Purpose – The study investigated coding agricultural education for innovative information and communication technology in Colleges of Education in Benue and Nasarawa States Nigeria. Method – The study employed a descriptive survey design. Three research questions were formulated to guide the study. The population of the study was 51 lecturers from the Colleges of Education in the study area. There was no sampling as all the populations were used as respondents. The instrument used for data collection was a 22 items questionnaire developed from literature reviewed titled “CAEITQ” (Coding Agricultural Education for Innovative ICT questionnaire). The Cronbach Alpha method of reliability was used to determine the internal consistency of the instrument and a reliability coefficient of 0.77 was obtained. Results – Findings from the study revealed that respondents required all the items on digital design and data visualization, digital programming and coding analysis and digital product management skills in coding agricultural education for innovative ICT in Colleges of Education. Conclusion – It was concluded that coding agricultural education for innovative ICT is the most potent weapon for paradigm shift from the traditional method of teaching and learning by both lecturers and students. Recommendations – It was recommended amongst others that lecturers of Agricultural Education in the various Colleges of Education be trained in digital programming and coding analysis in agricultural education for effective teaching and learning. Research Implications – The implication of this study is that utilization of digital coding, design, visualization, and programming skills in agricultural education will enhance effective teaching by lecturers in the area of study.